[Kościół św. Katarzyny w Gdańsku] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia kościół Św. Katarzyny od poł. zach. widoczny fragment ul. Podmłyńskiej (Kleine Mühlengasse), ok. 1900 r.